Daniel's true desire - Burrowes, Grace (Burrowes, Grace. True gentlemen., 2015)
Daniel Banks is a man of the cloth whose vocation is the last comfort he has left-and even his churchman's collar is beginning to feel like a noose. At the urging of family, Daniel attempts to start his life over as vicar in the sleepy Kentish town of Haddondale, family seat to the earls of Bellefonte. Resigned to spinsterhood, Lady Kirsten Haddonfield welcomes the new vicar to stay at her family's home while his is under renovation. Suddenly the handsome visitor has Kirsten rethinking her ideas about love and marriage, but a dreadful secret from Daniel's past may cast a shadow too long for either of them to overcome.